Levels of Cadmium, Copper, and Lead in Soils and Cassava Tubers Grown in Machakos County, Kenya - E. M. Kasyoka; G. W. Mbugua; R. N. Wanjau; G. N. Nambafu; J. N. Ndiritu (Applied and Environmental Soil Science)
Large quantities of agrochemicals are regularly applied in coffee farms to control pests and diseases and provide adequate nutrients to boost yields. Agrochemicals have varied amounts of heavy metals and their prolonged use to attain maximum yields contributes to the contamination of soil, surface, and groundwater. The study determined the levels of lead, cadmium, and copper in soil and cassava tubers (Manihot esculenta) grown in single-cropped and intercropped farms in Kathiani Subcounty, Machakos County, Kenya. Soil and cassava tuber samples were obtained in a zigzag of five cores across the farms. Cadmium, copper, and lead levels in the collected samples were determined using the atomic absorption spectrometer (AAS) Shimadzu AA-6200 model. Data were presented using tables and figures. One-way ANOVA was used to examine the mean differences of heavy metals between locations. Significant treatment difference was tested at α = 0.05 using the Tukey test. The results revealed that soils from single-cropped farms had a range of 0.09–0.59, 4.1–4.6, and 0.021–0.032 mg·kg−1 for cadmium, copper, and lead, respectively, while soils from intercropped farms had a range of 0.25–0.83, 4.9–10.1, and 0.022–0.037 mg·kg−1 for cadmium, copper, and lead, respectively. Considering cassava tubers in the single-cropped system, the mean values (mg·kg−1) of Cd, Cu, and Pb for the pith were 4.7, 6.8, and 0.028, for the bark were 4.4, 4.3, and 0.02, and for the epidermis were 3.1, 4.0, and 0.02, while flesh had 2.6, 1.4, and 0.05, respectively. Analysis of the tubers in the intercropped system indicated that the pith had a mean value of 7.8, 7.0, and 0.20 mg·kg−1 for Cd, Cu, and Pb, respectively. Similarly, the bark had 5.8, 4.6, and 0.16 mg·kg−1 for cadmium, copper, and lead. The epidermis indicated a concentration of 5.1, 4.6, and 0.12 mg·kg−1 for cadmium, copper, and lead, while the flesh had 2.8, 1.5, and 0.06 mg·kg−1, respectively. The results revealed the presence of heavy metals in both single-cropped and intercropped farms. The observed means for cadmium, copper, and lead in both sets of farms were within the WHO recommended levels for agricultural soils. However, the study observed higher cadmium, copper, and lead levels in soils and cassava tissues from intercropped farms compared to single-cropped farms.